Cleaner production and effluent management in flour plants and fish oil - Paredes Concepción, Perla (2014)
The implementation of environmental strategies such as Cleaner Production in operations, specifically plants producing fishmeal and fish oil, fisheries sector has generated a significant reduction of pollution to the marine environment through the recovery of valuable compounds present mainly in effluents were returned to the sea and are now introduced in the main process, thereby improving not only environmental performance but also increasing productivity contributing positively on the image of the organization to the stakeholders.